Kelekatan tidak aman dan cyberchondria pada dewasa awal: kecemasan kesehatan sebagai mediator - Putu Angita Gayatri; Atika Dian Ariana (Jurnal Psikologi Tabularasa, 2024)
ABSTRACTEarly adults are the highest internet health information seekers in Indonesia. Some people search the Internet excessively or repetitively for health information, which causes stress and/or anxiety. This phenomenon is called Cyberchondria. Attachment is thought to be at least indirectly related to Cyberchondria This cross-sectional study aims to determine the relationship between Insecure Attachment and Cyberchondria with Health Anxiety as a mediator. A total of 165 participants completed the Experience in Close Relationship-Revised (ECR-R), Short Health Anxiety Inventory (SHAI), and Cyberchondria Severity Scale-12 (CSS-12) questionnaires. Health Anxiety partially mediated the relationship between Anxious Attachment dimension and Cyberchondria (B=0.0430, CI95[0.0122; 0.0683], p=0.003). Health Anxiety did not mediate the relationship between Avoidant Attachment dimension and Cyberchondria (B=0.0200, CI95[-0.0360; 0.0680], p=0.437). However, Avoidant Attachment dimension can directly explain Cyberchondria (B=0.0843, CI95[0.0200; 0.1795], p=0.034). Suggest that each dimension of Insecure Attachment is related and can explain Cyberchondria although by different mechanisms. These results have implications for the development of understanding of the phenomenon of cyberchondria, especially from a developmental theory perspective.ABSTRACTIndividu dewasa awal merupakan pengguna internet tertinggi dalam mencari informasi kesehatan di Indonesia. Sejumlah orang mencari informasi kesehatan secara berlebihan atau berulang-ulang di internet yang kemudian memunculkan tekanan dan/atau kecemasan. Fenomena ini disebut Cyberchondria. Attachment diduga berhubungan setidaknya secara tidak langsung dengan Cyberchondria. Penelitian cross-sectional ini dilakukan untuk mengetahui hubungan Insecure Attachment dan Cyberchondria dengan Health Anxiety sebagai mediator. Sejumlah 165 partisipan melengkapi kuesioner Experience in Close RelationshipRevised (ECR-R), Short Health Anxiety Inventory (SHAI), dan Cyberchondria Severity Scale-12 (CSS-12). Hasil menunjukkan bahwa Health Anxiety memediasi secara parsial hubungan dimensi Anxious Attachment dan Cyberchondria (B=0,0430, CI95[0,0122; 0,0683], p=0,003). Namun, Health Anxiety tidak memediasi hubungan dimensi Avoidant Attachment dan Cyberchondria (B=0,0200, CI95[-0,0360; 0,0680], p=0,437). Walaupun demikian, Avoidant Attachment dapat menjelaskan secara langsung Cyberchondria (B=0,0843, CI95[0,0200; 0,1795], p=0,034). Disimpulkan masing-masing dimensi Insecure Attachment berhubungan dan dapat menjelaskan Cyberchondria meskipun dengan mekanisme berbeda. Temuan ini berimplikasi pada perkembangan pemahaman fenomena Cyberchondria, terutama melalui perspektif teori perkembangan.